Ardeshir Dadysett Pyaav at Jijamata Udyan - Ghosh, Ayan (2023)
There are four pyaavs inside the Jijamata Bhonsle Udyan that have been restored and are fully functional, serving drinking water to visitors. Two pyaavs were erected in memory of Ardeshir Dadysett, one in memory of Seth Samaldas Narsidas, and the fourth in memory of Khimji Mulji Randeria.